Assessment of cuspal deflection and microleakage in Class II composite restorations: Comparative analysis between nanocomposite and bulk-fill composite resin - Abhijit Ghosh; Priti D. Desai; Ipsita Maity; Paromita Mazumdar (Journal of Oral Research and Review)
Background: Composite resins are widely used for esthetic dental restorations, but polymerization shrinkage can cause cuspal deflection and microleakage, compromising restoration longevity. Aim: The study aimed to evaluate cuspal displacement and marginal leakage in Class II restorations employing bulk-fill composite resin (Filtek Bulk Fill) and nanocomposite (Filtek Z350 XT). Materials and Methods: Thirty-two intact maxillary first premolars obtained immediately postextraction were embedded 3 mm below the cementoenamel junction in acrylic resin. Two composite-filled plastic molds were fixed on the palatal and buccal cusps as points of reference, and buccopalatal widths (BPWs) were measured using a digital micrometer. Standardized Class II mesio–occluso–distal (MOD) cavities (2 mm width and 2 mm depth) were prepared and restored with either nanocomposite (Group A) or bulk-fill composite (Group B). After restoration, BPWs were remeasured to assess cuspal deflection. Samples underwent 500 thermal cycles (5°C–55°C), were stained with 2% methylene blue, and sectioned for microleakage analysis under a stereomicroscope at ×20. Differences between the groups were analyzed, with a significance level of 5%. Results: Group A exhibited a greater average cuspal deflection (0.144 ± 0.26 mm) compared to Group B (0.07 ± 0.16 mm), even though this discrepancy was not notably significant (P = 0.3). After thermocycling, Group A also had greater cuspal deflection (P = 0.61) and higher median microleakage (1.5 [1–2.75]) compared to Group B (P = 0.46). Conclusion: Nanocomposite showed higher cuspal deflection and microleakage than bulk-fill composite in large MOD cavities, although these differences were not statistically significant.